Serotype identification of Australian bluetongue viruses using a rapid fluorescence inhibition test. - Blacksell, S; Lunt, R (1993)
Rapid serotyping of bluetongue virus (BTV) isolates is required to facilitate the choice of an appropriate serotype-specific vaccine in a disease situation or to improve surveillance of BTV serotype prevalence. This communication describes the development and validation of a bluetongue virus fluorescent inhibition test (BTV FIT) as a rapid method to serotype Australian BTV isolates. The BTV FIT uses virus neutralisation principles similar to those used in the rabies rapid fluorescent focus inhibition test. The BTV FIT has the ability to provide an accurate serotype identification within 24 h thereby abbreviating the serotyping process by 3-4 days relative to conventional virus neutralisation assays and making the BTV FIT comparable time-wise with the polymerase chain reaction technique. The development of the BTV FIT is described using BTV reference viruses which have been isolated in Australia, and validation of the assay by assessment of five Australian BTV isolates of unknown serotype by comparison with the plaque inhibition method. The use of the BTV FIT readily facilitated rapid and accurate serotype identification of Australian BTV reference viruses and five unknown BTV isolates with results indicating full agreement with the plaque inhibition method.